2001
DOI: 10.1002/gcc.1099
|View full text |Cite
|
Sign up to set email alerts
|

TCL1 is activated by chromosomal rearrangement or by hypomethylation

Abstract: TCL1 is an oncogene activated by recurrent reciprocal translocations at chromosome segment 14q32.1 in the most common of the mature T-cell malignancies, T-cell prolymphocytic leukemia. It acts to transport Akt1 to the nucleus and enhance Akt1's serine-threonine kinase activity. TCL1 is also expressed in the B-cell malignancy, Burkitt's lymphoma (BL). However, 14q32.1 breakpoints have not been detected in BL, and we therefore investigated in more detail how expression was activated. No evidence for rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 20 publications
(21 reference statements)
3
41
0
1
Order By: Relevance
“…Site Determination-A transcription initiation site has been suggested at 41 bp downstream of a putative TATA box based upon the initial reverse transcriptase-PCR cloning of the TCL1 cDNA (1,15). However, the TCL1 start site has not been experimentally determined, and this position would be inconsistent with known start sites from TATA box-dependent promoters, which are generally 25-30 nucleotides downstream of the first T in the TATA sequence (reviewed in Refs.…”
Section: Tcl1 Transcriptional Startmentioning
confidence: 99%
See 3 more Smart Citations
“…Site Determination-A transcription initiation site has been suggested at 41 bp downstream of a putative TATA box based upon the initial reverse transcriptase-PCR cloning of the TCL1 cDNA (1,15). However, the TCL1 start site has not been experimentally determined, and this position would be inconsistent with known start sites from TATA box-dependent promoters, which are generally 25-30 nucleotides downstream of the first T in the TATA sequence (reviewed in Refs.…”
Section: Tcl1 Transcriptional Startmentioning
confidence: 99%
“…1) (47). Based on differential sensitivity at a single NotI restriction enzyme site in this core promoter, Yuille et al (15) previously concluded that TCL1 silencing was mediated by CpG methylation. Their finding that TCL1 expression was activated in silenced cells by 5-AC treatment was advanced as further support for this conclusion, although this reactivation experiment does not distinguish between direct and indirect effects resulting from 5-AC treatment.…”
Section: Tcl1 Transactivation By Sp1mentioning
confidence: 99%
See 2 more Smart Citations
“…The promoter region of the TCL-1 gene contains methylated CpG sequences in mature (IgM ϩ ) B cells and in acute T cell leukemia lines (26). We have tested the methylation status of five CpG sites at and around the NotI site of the TCl-1 promoter by pyrosequencing the bisulfite-treated genomic DNA.…”
Section: Tcl-1 Expression Inmentioning
confidence: 99%